2001
DOI: 10.1021/bi015698n
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E, a Prohormone Sorting Receptor, Is Anchored to Secretory Granules via a C-Terminal Transmembrane Insertion

Abstract: Carboxypeptidase E (CPE) is a sorting receptor that directs the prohormone pro-opiomelanocortin (POMC) to the regulated secretory pathway, and is also a prohormone processing enzyme in neuro/endocrine cells. It has been suggested that the 25 C-terminal amino acids are necessary for the binding of CPE to secretory granule membranes, but its orientation in the membrane is not known. In this study, we examined the structure and orientation of the membrane-binding domain at the C-terminus of CPE. In vitro experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 34 publications
3
70
0
Order By: Relevance
“…The luminal domain of the membrane form of CPE acts as a sorting receptor for targeting BDNF to the regulated secretory pathway vesicles in hippocampal and cortical neurons (Lou et al 2005). Membrane CPE can also exist in vesicles as a transmembrane protein with a cytoplasmic tail of ~10 amino acids at the C-terminus (Arnaoutova et al, 2003;Dhanvantari et al, 2002;Wu et al, 2004). The CPE cytoplasmic tail was found to interact with an activated form of the cytoplasmic small GTPase, Arf6, to recycle CPE and a CPE binding protein, eosinophil cationic protein, from the plasma membrane to the TGN in stimulated neuroendocrine cells (Arnaoutova et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The luminal domain of the membrane form of CPE acts as a sorting receptor for targeting BDNF to the regulated secretory pathway vesicles in hippocampal and cortical neurons (Lou et al 2005). Membrane CPE can also exist in vesicles as a transmembrane protein with a cytoplasmic tail of ~10 amino acids at the C-terminus (Arnaoutova et al, 2003;Dhanvantari et al, 2002;Wu et al, 2004). The CPE cytoplasmic tail was found to interact with an activated form of the cytoplasmic small GTPase, Arf6, to recycle CPE and a CPE binding protein, eosinophil cationic protein, from the plasma membrane to the TGN in stimulated neuroendocrine cells (Arnaoutova et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous integral or membranebound proteins were identified, including several involved in vesicle trafficking and cytoskeletal proteins, as expected. However, potential sorting receptors such as SgIII (Han et al 2008) or carboxypeptidase E (Dhanvantari et al 2002) were not identified in parotid membranes by this method. Nonetheless, one salivary cargo protein, PSP, was identified.…”
Section: Parotid Secretory Protein (Psp) Binds To Secretory Granule Mmentioning
confidence: 87%
“…CPE itself binds the granule membrane. The C-terminus of CPE can span the membrane, although only 5 amino acid residues are cytosolic (Dhanvantari et al 2002). Recycling of CPE from the plasmalemma requires ARF6 apparently due to direct binding to the coat protein.…”
Section: Selective Trafficking For Secretionmentioning
confidence: 99%
“…These include paired basic residues that may interact with granule-resident PC enzymes (14, 24 -26), N-terminal disulfide-bound loops (27,28), and other domains that mediate sorting by binding to caboxypeptidase E (2), calcium-binding domains that lead to aggregation (reviewed in Ref. 8), and ␣-helices that either traverse or interact with membranes (3,(5)(6)(7). Finally, proteins may contain more than one single type of sorting domain so that analyses in which any one of these is eradicated will not eliminate sorting in the context of the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…This process, called regulated secretion, depends on a highly selective triage of proteins within or just after the TGN. Retention in dense core secretory granules is not a random process and granulesorted proteins must possess unique properties or must interact with other cellular components in a unique way to end up in this organelle (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%